STEM CELL PADA CEDERA OTAK TRAUMATIK - Khairunnisa Ichwan; Ainul Riza (CV. Adiba Aisha Amira, 2023)
Traumatic brain injury is a mechanical trauma to the head, either directly or indirectly, which causes impaired neurological function, namely physical, cognitive, psychosocial functioning, both temporarily and permanently. Traumatic brain injury is a very complex disease. Currently, there is no effective treatment that can reduce the effects of the primary injury, only therapy that can inhibit its development. Interventions to improve the quality of life of traumatic brain injury patients used to include drug treatment, surgery, and rehabilitation therapy have had poor results. The recent clinical use of stem cells as a possible therapeutic application. Stem cell therapy is used in regenerative medicine to restore damaged neurons. Stem cell is a cell that exhibits a multipotent capacity to differentiate into different cell types and has the capacity for self-renewal. In different preclinical studies, conducted in animal models of traumatic brain injury, stem cell transplantation has led to improvements in several neurological parameters. Mesenchymal stem cell therapy is one of the most potent and attractive options for regenerative therapy of traumatic brain injury. This therapy has shown its potential in clinical aspects. Although there is much basic research on traumatic brain injury, especially on the complex pathophysiology and applicability of stem cell therapy, there are still many issues that need to be resolved to determine the best method for recovery of brain function.